Designing seed mixtures for restoration on alpine soils: who should your neighbours be?. Issue 3 (12th April 2017) - Rydgren, Knut; Hagen, Dagmar; Rosef, Line; Pedersen, Bård; Aradottir, Asa L.
Abstract: Questions: (1) When alpine vegetation is actively restored by seeding, how is vegetation cover influenced by seeding treatments and soil conditions? (2) How does the cover of species differ when they are seeded in a mixture and how is their response influenced by soil conditions? (3) Do individual species perform better or worse in a mixture than when sown separately? Location: Hjerkinn, Dovrefjell, Norway. Methods: In a factorial, randomized field experiment, we recorded the percentage cover of Festuca ovina, Luzula multiflora subsp. frigida and Poa alpina seeded in four different soil types for 3 yr after seeding. We seeded the three species separately and in a mixture in organic topsoil, peat soil, mineral fine soil and mineral coarse soil. We also recorded seedling emergence in a greenhouse experiment, using the same seeding treatments. Results: In the field experiment, vegetation cover established fastest when F. ovina was sown in monoculture, followed by the seed mixture. After 3 yr, mean cover of F. ovina was 1.4 times higher than mean P. alpina cover and more than three times higher than mean L. multiflora cover for single species treatments, and four ( P. alpina ) and 15 ( L. multiflora ) times higher when the species were seeded together. L. multiflora germinated slowly in the greenhouse experiment, which could partly explain its poor field performance. In the field experiment, establishment was faster in organic soils than mineral soils for all seeding treatments. The largest difference between F. ovina and L. multiflora performance in the mixture treatment was found in the organic soil types, where overall cover was larger than in the mineral soils. In the organic soils, F. ovina was slightly facilitated in the mixture treatment, while the opposite was found for L. multiflora . Conclusion: When the restoration goal is to quickly establish a vegetation cover, seeding monocultures of rapidly establishing species may be more effective than seeding mixtures, even in alpine sites, where interspecific facilitation may prevail. Abstract : In an alpine field experiment, we studied how four different seeding treatments (single species and in mixture) in four different soil types affected percentage cover of the seeded vegetation after three years. There were large differences both between seeding treatments, with single seeded Festuca ovina achieving the largest cover, and between soil types. A result with implication for alpine restoration.